The involvement of microglia in Alzheimer's disease: a new dog in the fight - Moore, Zachery (Br J Pharmacol, 2018)
First described clinically in 1906, Alzheimer's disease (AD) is the most common neurodegenerative disease and form of dementia worldwide. Despite its prevalence, only five therapies are currently approved for AD, all dealing with the symptoms rather than the underlying causes of the disease. A multitude of experimental evidence has suggested that the once thought inconsequential process of neuroinflammation does, in fact, contribute to the AD pathogenesis. One such CNS cell type critical to this process are microglia. Plastic in nature with varied roles, microglia are emerging as key contributors to AD pathology. This review will focus on the role of microglia in the neuroinflammatory response in AD, highlighting recent studies implicating aberrant changes in microglial function in disease progression. Of critical note is that with these advances, a reconceptualization of the framework in which we view microglia is required. LINKED ARTICLES: This article is part of a themed section on Therapeutics for Dementia and Alzheimer's Disease: New Directions for Precision Medicine. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v176.18/issuetoc